2013
DOI: 10.1002/gps.4036
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of FDG‐PET and blood flow SPECT in the diagnosis of neurodegenerative dementias: a systematic review

Abstract: Overall, although studies suggest superiority of PET over SPECT, the evidence base for this is actually quite limited. We suggest that further direct comparative studies, including health economic and patient preference evaluations, are needed to help direct future service provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 65 publications
0
51
0
2
Order By: Relevance
“…In this study, PET with or without 11 C-PIB brain imaging helped improve the accuracy of diagnosis of dementia subtype in 36% of our patients with underlying Alzheimer's disease, dementia with Lewy bodies, vascular dementia, and frontotemporal dementia.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In this study, PET with or without 11 C-PIB brain imaging helped improve the accuracy of diagnosis of dementia subtype in 36% of our patients with underlying Alzheimer's disease, dementia with Lewy bodies, vascular dementia, and frontotemporal dementia.…”
Section: Discussionmentioning
confidence: 87%
“…11 In a systematic review, the sensitivity and specificity for 18 F-FDG PET in distinguishing between AD and DLB was 83%-99% and 71%-93%, respectively; and the sensitivity and specificity for 18 F-FDG PET in distinguishing between AD and FTD was 97.6%-99% and 65%-86%, respectively. 11 In the same systematic review, 18 F-FDG PET predicted patients with mild cognitive impairment (MCI) deteriorating into dementia with sensitivity and specificity of 81%-82% and 86%-90%, respectively. 11 Besides, 11 C-PIB can detect the presence of fibrillar amyloid plaques that are a neuropathological marker of AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies for 18 F-FDG PET generally report higher accuracy, with sensitivities of 75%-99% for AD and specificities of 71%-93% (9). However, there have been few direct head-to-head comparisons, limited by small sample sizes and showing mixed results (10). For example, although some studies have suggested slight superiority of 18 F-FDG PET for diagnostic accuracy, in the largest study to date, both HMPAO SPECT and 18 F-FDG PET were able to completely separate all 26 AD cases from controls (11).…”
mentioning
confidence: 99%